Metode Monte Carlo dalam Memprediksi Produksi Es Balok terhadap Optimalisasi Kebutuhan - Muhammad Habib Yuhandri (Jurnal Informasi dan Teknologi, 2022)
The simulation in predicting the production of Ice Cube is an estimate of the calculation of the production level of Ice Cube. This simulation can predict the production of Ice Cube to meet customer demand in the future compared to just guessing. PT. Fisheries Indonesia is a state-owned company and one of its branches is in Padang City which is specifically for producing Ice Cube to meet the needs of the West Sumatra area. The purpose of this study is to predict the production of Ice Cube which is useful for knowing the next production so that it can increase efficiency in terms of cost and time and can also optimize needs. The data used in this study is Ice Cube production data in 2019 and 2021 which is processed using the Monte Carlo method. The Monte Carlo method is a numerical method that is described as a statistical simulation method, which will calculate the production frequency, then calculate the probability distribution and cumulative probability then calculate the range of values, after that a simulation is carried out using a number of random variables. The results of the simulations that have been carried out in predicting the production of Ice Cube obtained an accuracy rate of 85% for 2019 and 90% for 2020. Based on the results of the research conducted, it is hoped that it will make it easier for PT Fisheries Indonesia Padang Branch to determine the amount of Ice Cube production.